Pipes, taps and vendors: An integrated water management approach - Georg Meran; Markus Siehlow; Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This paper applies a microeconomic-based stylized model to identify the optimal modal split of water supply infrastructure in regions of the Global South against the background of the Sustainable Development Goal (SDG) No. 6. We assume a linear city, with some plausible assumptions on income and willingness-to-pay, and then calculate the optimal tap density, leading in turn to an optimal modal split between piped and unconnected water consumption. From an economic perspective, not all water users need to be connected to a centralized, pipeline infrastructure, and the non-connected households should be served by non-mobile or mobile vendors. The analysis is firstly made for the case of totally inelastic demand functions for simplification reasons and afterwards the analysis becomes more complicated and realistic by addressing elastic demand functions which are based on a simplified version of the Stone-Geary utility function. In terms of policy implications, the paper suggests a role for decentral, offgrid solutions to generalized water supply, with a certain role for water vendors.
Keywords: C31; R12; O17; Q25; 330; Water; Infrastructure; mobile vendors; integrated planning; informal economy